Perfil epidemiológico de los adultos mayores de una unidad de larga estancia: Asilo León Ruales 2017 Ibarra – Ecuador: Epidemiological profile of senior adults of a long stay unit: Asilo León Ruales 2017 Ibarra – Ecuador (La U Investiga, 2018)
Introduction: Older adults belong to a segment of the vulnerable population, mainly due to the presence of chronic comorbidity, with a higher risk of presenting geriatric syndromes such as cognitive deterioration or dementia, falls, dysmobility, depression, urinary incontinence, hypertension, diabetes, pressure ulcers, etc. Objective: To identify the prevalent pathologies in older adults admitted to a long-stay unit in the city of Ibarra, through the integral geriatric assessment process, which allowed defining the needs of care and medical and nursing intervention in the elderly population. The study population. Materials and methods: An observational, qualitative and quantitative cross-sectional study was carried out in the “León Ruales” Asylum through the creation of a database in the Excel 2016 program, which were extracted from the review of medical records older adults, which was exported to the IBM SPSS Statistics version 23 statistical software.RESULTS AND CONCLUSIONS: The distribution according to sex was more prevalent among older adults in the age range of 81-90 years. As neurological deterioration, the most prevalent pathology and in a considerable percentage of older adults were evidenced by complementary examinations, alteration of renal function and corroborated other diagnoses such as: Anemia, Hyperglycemia, Hypoalbuminemia.
Keywords: Epidemiological profile; elderly; dementia; aging; comorbidity